Analisa Kinerja Satuan Pengawasan Internal (SPI) dalam Pengelolaan Keuangan pada RSUD Ibnu Sina Kabupaten Gresik - Ardiansyah, Muhammad Bagus; Reviandani, Wasti (MES Bogor, 2024)
This study aims to analyze the performance of the Internal Audit Unit (SPI) in financial management at Ibnu Sina Regional General Hospital (RSUD) in Gresik Regency. The research focuses on evaluating the effectiveness of SPI's duties, identifying challenges faced, and proposing solutions to improve performance in supporting financial transparency and accountability. The study employs a qualitative approach with data collected through in-depth interviews with SPI members, the head of the finance department, and the head of the accounting sub-section at RSUD Ibnu Sina. The findings reveal that SPI has not been functioning optimally due to several factors, such as insufficient incentives, limited training opportunities, the absence of a dedicated workspace, and an inadequate number of personne relative to their workload. Additionally, the lack of regular audit schedules and SPI's minimal involvement in identifying financial risks are significant challenges.